2023
DOI: 10.3390/drones7030183
|View full text |Cite
|
Sign up to set email alerts
|

Deep Learning-Based Pine Nematode Trees’ Identification Using Multispectral and Visible UAV Imagery

Abstract: Pine wilt disease (PWD) has become increasingly serious recently and causes great damage to the world’s pine forest resources. The use of unmanned aerial vehicle (UAV)-based remote sensing helps to identify pine nematode trees in time and has become a feasible and effective approach to precisely monitor PWD infection. However, a rapid and high-accuracy detection approach has not been well established in a complex terrain environment. To this end, a deep learning-based pine nematode tree identification method i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…These attention mechanisms enable the network to capture finer target-related details, thereby improving the model’s ability to perceive information. Qin et al ( Qin et al., 2023 ). achieved high accuracy in detecting pine wilt diseased trees based on improved YOLOv5 combined with attention mechanisms such as CBAM.…”
Section: Discussionmentioning
confidence: 99%
“…These attention mechanisms enable the network to capture finer target-related details, thereby improving the model’s ability to perceive information. Qin et al ( Qin et al., 2023 ). achieved high accuracy in detecting pine wilt diseased trees based on improved YOLOv5 combined with attention mechanisms such as CBAM.…”
Section: Discussionmentioning
confidence: 99%
“…The above research projects are based on image processing and recognition of RGB images, while some groups leverage the high dimensional feature in multi-spectral images. Qin et al [83] and Park [84] use drones mounted with multi-spectral cameras for training data collection and conducting deep neural network detection.…”
Section: Pine Wilt Detectionmentioning
confidence: 99%
“…UAVs have been used in remote sensing to detect and segment numerous types of objects and different environments, such as agricultural fields, urban areas, forests, and bodies of water, providing valuable data for various applications including environmental monitoring, disaster management, and infrastructure inspection [ 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. These technological tools, often accompanied by classical machine learning (ML) and deep learning (DL) methodologies, enhance the accuracy and efficiency of different vegetation mapping [ 18 , 19 , 20 , 21 , 22 , 23 ]. Studies have demonstrated the effectiveness of employing DL for accurately monitoring and classifying these delicate species like moss and lichen in diverse environmental settings [ 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%